1965
DOI: 10.1002/app.1965.070090503
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hydroperoxides in ultraviolet-irradiated nylon 66

Abstract: SynopsisAccording to mechanisms described in the literature, photodecomposition of nylon 66 proceeds through the abstraction of the hydrogen on the carbon u to the amide NH group by a free radical which has been activated by photo absorption. In the p r o p agation phase, the a-carbon radical could readily react with atmospheric oxygen to form a hydroperoxide. The formation of a hydroperoxide in the photodecomposition scheme for nylon 66 has been detected but has not been measured quantitatively.With the color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Interest in the processing of wool and wool blends on the short staple system [ 1,2,3,5,9] has increased because of apparently higher profit from these yams [7] compared to those made by conventional methods. Short staple wool is scarce and so the available wool must be shortened by cutting or stretch-breaking the fibers in the sliver state [8], These fiber-shortening methods add to cost, however, because the wool must be processed into tops before the fibers can be shortened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in the processing of wool and wool blends on the short staple system [ 1,2,3,5,9] has increased because of apparently higher profit from these yams [7] compared to those made by conventional methods. Short staple wool is scarce and so the available wool must be shortened by cutting or stretch-breaking the fibers in the sliver state [8], These fiber-shortening methods add to cost, however, because the wool must be processed into tops before the fibers can be shortened.…”
Section: Discussionmentioning
confidence: 99%
“…This lamp emits radiation from 3500-6500 A, so photodegradation of nylon should proceed via photo-oxidation. This is because many researchers have reported that incident radiation of a wavelength longer than 3000 A causes photo-oxidation of the polymer [ 1,22,23,27].…”
Section: Photodegradation Using An Mbtf Lampmentioning
confidence: 99%
“…The absorbance of the carbonyl band generally falls between 1900 and 1600 cm −1 and the reference peak can be the CH 3 rocking band or the CH 2 scissoring band which correspond to vibrations of groups not affected by oxidation [44,[51][52][53][54]. High CI indicates a high degree of polymer degradation [53].…”
Section: Carbonyl Index (Ci) =mentioning
confidence: 99%
“…This is equivalent to about 10 5 xenon strobe flashes over the display lifetime of undyed nylon. Anton (1965) showed that 20 hours of exposure to light between 340 and 415 nm caused a detectable decrease in tensile strength of undyed nylon-6,6 samples. Based on data for the Atlas Weather-Ometer xenon source, this exposure amounted to approximately 3  10 21 nearultraviolet plus blue photons/cm 2 .…”
Section: Polystyrenesmentioning
confidence: 99%